Semantic differences between the vocabulary of Quran (Journal of the College of Education for Women, 2019)
Ceremony of the Koran vocabulary animate different connotations unique style patch onsmth not any method of Arabs, has been used used vocabulary and special Madza, he putevery single in place of installation so that if you do not put in place misfire meaning andbecame Rkika method. Our goal in this research study a range of vocabulary in terms of theimplications and documenting the trial of the Hadith and sayings of the beneficiaries of Arabscholars have different attitudes, linguists and interpreters and speakers and fundamentalists,philosophers, and others.